Development of a New Discretization Drum - Jumaniyazov Qadam Jumaniyazovich; Yuldashev Jamshid Qambaraliyevich; Sardor Tojimurodov Ilxom ogli (Genius Journals, 2023)
In this article, based on the research of the discretizing drum of a pneumomechanical spinning machine, the problems of creating a discretizing drum of a new design, which can increase the speed of the discretization process, reduce the degree of breakage of fibres, and effectively clean the skein supplied with fibres from small impurities, are considered.
Keywords: pneumomechanics; discretization; fibre; damage